Continuing medical and student education in dermatology during the coronavirus pandemic – a major challenge. (27th July 2020) - Martin, Alice; Lang, Estefanía; Ramsauer, Babett; Gröning, Thilo; Bedin, Gustavo L.; Frank, Jorge
Summary: Continuing medical education (CME) is the essential basis for student teaching and for training and further development of physicians. Without it, modern and adequate patient care is unthinkable. Recently, the coronavirus pandemic, caused by the severe acute respiratory syndrome coronavirus 2 (SARSCoV2), forced the entire medical community to change its usual habits of advanced medical training, teaching and learning. As a result, digital training and teaching via social media, online medical encyclopedias, web‐based learning platforms and educational podcasts moved to the fore. Here, we give an overview on current concepts for online medical education, with special consideration of dermatology.